2021
DOI: 10.3389/fpubh.2020.561264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptom Differences Between Mild and Severe COVID-19 Patients in China: A Meta-Analysis

Abstract: Objective: The prognosis of mild and severe patients has prominent differences during the prevalence of COVID-19, and it will be significant to identify patients' potential risk of progressing to severe cases according to their first clinical presentations. Therefore, we aim to review the clinical symptoms of the COVID-19 epidemic systematically.Methods:We searched PubMed, Embase, Web of Science, and CNKI (Chinese Database) for studies about the clinical features of COVID-19 in China from March 18 to April 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 28 publications
4
51
0
7
Order By: Relevance
“…Thus, from our findings, we recommend close monitoring of patients who do not experience anosmia symptom, particularly those at high risk of disease progression such as elderly males with comorbidities, during the first week of COVID-19 symptom onset for early diagnosis of severity of illness. A meta-analysis demonstrated that initial COVID-19 symptoms such as fever, cough, dyspnea, diarrhoea, abdominal pain, anorexia, and fatigue are more frequently seen in severe COVID-19 patients compared to mild patients (He et al 2021 ). Our finding strongly suggests anosmia, along with other potential parameters could be a potential factor for predicting early COVID-19 severity, thereby facilitating early intervention and rational distribution of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, from our findings, we recommend close monitoring of patients who do not experience anosmia symptom, particularly those at high risk of disease progression such as elderly males with comorbidities, during the first week of COVID-19 symptom onset for early diagnosis of severity of illness. A meta-analysis demonstrated that initial COVID-19 symptoms such as fever, cough, dyspnea, diarrhoea, abdominal pain, anorexia, and fatigue are more frequently seen in severe COVID-19 patients compared to mild patients (He et al 2021 ). Our finding strongly suggests anosmia, along with other potential parameters could be a potential factor for predicting early COVID-19 severity, thereby facilitating early intervention and rational distribution of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Over 210 countries worldwide have been involved, with over 145 million infected subjects. People of all ages are susceptible to SARS-CoV-2 infection and experience mild (fever, cough, shortness of breath, muscle aches, loss of taste or smell, diarrhea) or severe symptoms, including pneumonia and acute respiratory distress syndrome (ARDS), with an elevated risk of death due to respiratory failure [3]. About 3.1 million deaths caused by SARS-CoV-2 infection have been registered so far, with up to 96% of dead people showing one or more comorbidities (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observation revealed that COVID-19 patients had different degrees of diarrhea, nausea, decreased appetite, rash, and other adverse reactions during antiviral treatment. [ 20 , 21 ] At the same time, to cutoff the transmission route, the confirmed patients accepted isolation treatment and other prevention and control measures, which leads to anxiety, stress, loneliness, depression, and despair. [ 20 ] Excessively negative emotions can result in obsessive thinking, and, in severe cases, psychopathy seriously affects the treatment and recovery of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%